The influence of a permanent magnetic field on the crystallization of calcium carbonate from carbonate aqueous solutions - Gayevskii, V.R.; Nechyporuk, B.D.; Gayevska, S.G. (Physics and Chemistry of Solid State, 2023)
The effect of a permanent magnetic field on the crystallization of calcium carbonate from carbonate aqueous solutions was studied. Based on the equations for the first- and second-order dissociation constants of carbonic acid, the stability constants of NaCO3- and NaHCO30 complexes, the mass balance and electroneutrality equations, the values of the system components and the ratio between the components of the carbonate subsystem were determined, and it was established that the main species in experimental conditions are СО32-, NaСО3- and HСО3- and the main components of the carbonate subsystem are СО32- (86.7%) and HСО3- (13.19%). Studies have shown that with a significant excess of CO32- over HCO3- ions in the solution at temperatures of 18-20˚C, calcite and vaterite are most likely formed. During the crystallization of calcium carbonate from an aqueous carbonate solution in a magnetic field of 125-250 mT, the size of the crystallites increases significantly compared to the absence of a magnetic field.